Prevalence of Acanthosis nigricans and Related Factors in Iranian Obese Children - Sayarifard, Fatemeh (J Clin Diagn Res, 2017)
INTRODUCTION: Recognition of Acanthosis nigricans (AN) provides important opportunities for screening of obesity syndrome, dyslipidemia, hypertension and insulin resistance with diabetes mellitus 2. Considering the high prevalence of obesity among Iranian children, we designed this study to estimate the prevalence of AN and related laboratory factors in Iranian obese children. MATERIALS AND METHODS: Seventy-one obese children were enrolled in this study. Diagnosis of AN was done by clinical examination. Body mass index (BMI), fasting blood sugar, total cholesterol, triglycerides (TG), alanine aminotransferase, aspartate aminotransferase (AST), alkaline phosphatase, high- and low-density lipoprotein cholesterol, insulin, thyroid-stimulating hormone, free thyroxin (fT4), calcium, phosphorus and 25-hydroxyvitamin D were measured with routine techniques. Collected data were compared between cases with AN and without AN. Independent t-test was used for comparison of variables. RESULTS: Twenty-five of children were female (35.2%). Forty-eight children (67.6%) had AN. In 20 cases (28.2%), homeostasis model assessment-insulin resistance (HOMA-IR) was <2.5 and in 51 (71.8%), HOMA-IR was more than 2.5. Mean BMI, insulin, HOMA-IR, TG and AST levels were significantly higher in cases with AN. CONCLUSION: Obese children with AN are at risk of developing diabetes. Hence early identification of this feature and precise evaluation of children is recommended.